Analisis Tingkat Pemahaman Warga terhadap Penggunaan Zat Kimia dalam Ruang Lingkup Rumah Tangga - Esa Suci Pratiwi; Rega Danica Azzahra; Salsabila Zahra Sugiono; Wini Nuraini (Universitas Palan, 2024)
The public perspective of chemistry, considered to be something that has always been associated with B3 or Toxic and Dangerous Substances, in fact this is not entirely true. Instead, our lives are surrounded by various kinds of chemicals. Both the molecules of the elements and the compounds, their existence is very close to ourselves. Inappropriate knowledge and attitudes toward the term chemicals are found in our society. But chemicals are not something that must be avoided, but used with careful rules. In reality, chemicals are very helpful in the various activities of life. Based on this, there should be an education such as socialization to people that chemicals are not always dangerous substances. The data was collected with qualitative techniques, through unstructured interviews related to the understanding of chemicals in the family sphere with some basic questions related to household chemicals as well as socialization activities concerning chemical substances in households to people of RT 05 RW 02 Cirejag Village, Karawang. The interview was conducted to obtain an explanation about how far they understand about the chemical in the household so that the socialization activities held are expected to help correct misperceptions and improve their understanding related to domestic chemicals.